2024
DOI: 10.31580/jmi.v9i3.2706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grit on workplace happiness: A moderated mediation model

Abstract: Employee happiness as well as well-being at the workplace is an emerging concept in the management and psychology domain. This article aims to analyze the impact of grit on employees’ workplace happiness via psychological capital (PsyCap), moderated by coaching culture and theorize by trait activation theory. Data were collected from 272 employees working in the public and private sectors of the service industry in Pakistan. For statistical analysis, we conducted reliability, correlation, and process Hayes. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is because workers who show greater commitment and interest in their work activities experience satisfaction with their performance and the results they obtain in the workplace. This sense of job satisfaction and achievement contributes to greater happiness and positive emotions in the work environment ( Shafique et al, 2023 ). Both constructs have a reciprocal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because workers who show greater commitment and interest in their work activities experience satisfaction with their performance and the results they obtain in the workplace. This sense of job satisfaction and achievement contributes to greater happiness and positive emotions in the work environment ( Shafique et al, 2023 ). Both constructs have a reciprocal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was shown that people who are more goal-oriented tend to be happy and satisfied with their lives, as they use persistence, consistency, and well-being as a foundation for career success ( Mazhar Khan and Khan, 2017 ). In addition, research on 272 workers in Pakistan reported that persistence and consistency of goal achievement was related to happiness at work and psychological capital, where the latter measure had a significant mediating effect on the relationship of the other two variables ( Shafique et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%